Is cartilage shield tympanoplasty better than fascia tympanoplasty - Sheikh, Shahnaz; Bajaj, Anushree; Vaze, Vikrant (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Temporalis fascia and cartilage are the most commonly used graft materials, though contradictory reports are available in literature as regards their efficacy in tympanoplasty. The aim of the study was to compare the graft uptake rates and hearing results in case of temporalis fascia and cartilage in type 1 tympanoplasty. Methods: A total of 400 cases with large, subtotal and total perforation were considered in the study. All the selected patients were divided into two groups. Group A in which temporalis fascia graft was used and including 200 cases and cartilage graft was used in Group B patients including 200 cases. Pure tone audiometry was performed preoperatively and postoperatively at 6 months. Results: The graft uptake rate was more than 90 percent and more than 80 percent in Group B respectively at the end of 14 week. There was no statistical difference in hearing improvement in both the groups. Conclusions: Tragal cartilage graft can be used in cartilage tympanoplasty especially in moderate, large and subtotal perforations. The graft has better uptake rate, less graft failure and hearing improvement results were comparable to temporalis fascia graft.